Improving the reliability of informationcontrol systems at power generation facilities based on the fractalcluster theory - Budanov, Pavlo; Brovko, Kostiantyn; Cherniuk, Artem; Vasyuchenko, Pavlo; Khomenko, Viktor (Eastern-European Journal of Enterprise Technologies, 2018)
We have developed a cluster model for the structure of an informational space as a combination of informational signals that carry information about emergency signs at a deviation of a technological process parameters at electric power facilities, based on the application of an apparatus of the fractal-cluster theory. A dynamic fractal cluster model is derived to describe processes in the informational space of information control systems in software technical complex of the automated control system for a technological process at a power plant. We have established functional dependences of the dynamics of change in the electro-physical magnitudes of technological parameters, such as current and voltage, on the informational fractal dimensionalities. Based on the application of a dynamic fractal cluster model, we detected random informational signals that make it possible to identify false triggering and failures of technological equipment. To estimate the reliability criterion in the functioning of information control systems in software technical complex of the automated control system of a technological process at power plants, we derived analytical dependences that connect a gain in the amount of information, fractal time and the informational fractal dimensionality. By determining the amplitude, phase, and frequency of random informational signals in real time, we established conditions for the signs of emergency and pre-emergency. The obtained theoretical and practical results have been demonstrated to improve the reliability of operation of information control systems in a software technical complex for automated control systems.